PRINCIPLE OF MUTUAL CONSIDERATION (PMC) IN AN ONLINE INDONESIAN EFL CLASSROOM INTERACTION TO PROMOTE QUALITY ONLINE LEARNING - Muhammad Rafi Abdusyukur, - (2022)
Classroom interaction is considered a vital factor in determining quality learning. Quality learning can be described as the measure of successful learning activities that can be determined by the achievement of the learning goals. Thus, the politeness aspect upheld by the classroom parties decides the effectiveness and smoothness of the classroom interaction in achieving the learning goals. Due to the COVID-19 pandemic that has transformed the EFL classroom online, the way the polite classroom interactions are delivered in the classroom has changed. This study investigated the realization of the politeness phenomenon in the Indonesian EFL online classroom by utilizing both FIACS (landers Interaction Analysis Category System) and PMC (Principle of Mutual Consideration). A qualitative research method with a case study design was employed. One teacher and a class of seven-grade students were involved as participants. The necessary data was collected through observations and interviews. The results indicates that most of the interactions happened in the Indonesian online EFL classroom fulfilled all of the principles of PMC to an extent that it supported the smoothness and effectiveness of the online interactions. However, violations of PMC also happened in the online interaction, especially the 'Criticize or justify authority' category by the teacher and 'Silence' category by the students. These violations delayed the attainment of the learning goals, hindering the realization of quality online EFL learning. In conclusion, this study revealed that the presence of all principles of PMC supported the promotion of quality online EFL learning even though technology also played a critical part in realizing it.